The influence of secreted factors and extracellular vesicles in ovarian cancer metastasis - Marta Hergueta-Redondo; Héctor Peinado (EJC Supplements, 2020)
Ovarian cancer cells mainly metastasise within the peritoneal cavity, the lethal consequence of tumour progression in this cancer type. Classically, changes in tumour cells, such as epithelial to mesenchymal transition, involve the down-regulatinon of E-cadherin, activation of extracellular proteases and integrin-mediated adhesion. However, our current understanding of ovarian tumour progression suggests the implication of both intrinsic and extrinsic factors. It has been proposed that ovarian cancer metastases are a consequence of the crosstalk between cancer cells and the tumour microenvironment by soluble factors and extracellular vesicles. Characterisation of the alterations in both the tumour cells and the surrounding microenvironment has emerged as a new research field to understand ovarian cancer metastasis. In this mini review, we will summarise the most recent findings, focusing our attention on the role of secreted factors and extracellular vesicles in ovarian cancer metastasis.